PENGARUH STRUKTUR MODAL, STRUKTUR KEPEMILIKAN SAHAM DAN PROFITABILITAS PAD A NILAIPERUSAHAAN SEKTOR KEUANGAN - Yulianto Umar Rofi’i; Hari Sukarno; Nurhayati Nurhayati (STIE Mandala Jember, 2017)
This study aimed to assess the effect of capital structure, institutional ownership, managerial ownership and profitability in the value of financial sector companies as well as test the consistency of effect of capital structure, institutional ownership, managerial ownership and profitability in the company’s value sub-sectors of banking, insurance and securities companies.This research is a quantitative approach to hypothesis testing (hypothesis testing). The data used in this research are secondary data from company financial statements in the financial sector the period 2010 - 2012. The data obtained from the website Indonesia Stock Exchange (IDX) on site as well as the Indonesian capital market www.idx.co.id directory (ICMD). The population in this study is the Banking, Insurance and Securities Companies listed on the Stock Exchange and have the publication of financial statements for 2010 to 2012. The sampling method used is a method of population census of all the research sample, up to a total of 35 financial companies sub-sector listed on the Stock Exchange 2010-2012.metode period used is multiple linear regression analysis. The results of this study demonstrate the consistency between the variables in the sectors of Banking, Insurance and Securities Company, that the capital structure has no effect on the Company Value of Financial Sector and profitability effect on Corporate Values Financial Sector, while the results of this study also showed no consistent effect of ownership on the value financial sector companies listed on the Stock Exchange 2010-2012.